1986
DOI: 10.1017/s0022215100099722
|View full text |Cite
|
Sign up to set email alerts
|

Involution of residual juvenile nasopharyngeal angiofibroma

Abstract: The apparent tendency of juvenile nasopharyngeal angiofibroma to involute with age has been known for many years but firm evidence of this has been lacking. This case report uses computerized tomography to provide the first documented evidence of this involution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

1989
1989
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 6 publications
0
18
0
Order By: Relevance
“…Stansbie et al [22] and other authors [23Á25] have demonstrated spontaneous involution of JNA in both treated and untreated lesions by serial CT scans. During the 23 years observation period of this study, the highest age at recurrence was 29 years, supporting the notion that the tumor eventually burns out by itself.…”
Section: Discussionmentioning
confidence: 89%
“…Stansbie et al [22] and other authors [23Á25] have demonstrated spontaneous involution of JNA in both treated and untreated lesions by serial CT scans. During the 23 years observation period of this study, the highest age at recurrence was 29 years, supporting the notion that the tumor eventually burns out by itself.…”
Section: Discussionmentioning
confidence: 89%
“…In the event of intracranial recurrence or residual disease, no fixed or standard approach to these patients is rec ommended because treatment must be tai lored to each individual case. It has been well documented in the literature that all recurrences are not life-threatening and many patients have been followed expec tantly without significant complications or morbidity [3,4,9,10,12,17], All recurrences in this series occurred with stage I and II disease probably due to inadequate surgical removal. All recurrences were treated surgically.…”
Section: Discussionmentioning
confidence: 90%
“…Treatment involves surgery, irradiation or hormonal therapy depending upon the staging and involvement. Spontaneous regression [9,10] has been noticed in individuals who are > 20 years old. Surgical management [11,12] is the primary treatment which is required in most of the cases.…”
Section: Discussionmentioning
confidence: 99%